Analisis Hukum Kepemilikan Tanah yang Dijadikan Setoran Modal Dalam Perseroan Terbatas - Pelupessy, Eddy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to find out, understand and explain the form of legal certainty regarding land participation as capital of a limited liability company and legal protection for land owners on which there are buildings which are used as capital participation in limited liability companies. This research uses a normative (applied) juridical approach. This approach is motivated by the idea that law cannot be separated from people's lives in the form of values and attitudes/behavior carried out (law is not autonomous). The results of the juridical and socio-cultural approaches are accumulated in an analytical framework to develop a new idea about land ownership which is used as capital contribution in a Limited Liability Company. The results of this research reveal that the form of legal certainty regarding the inclusion of buildings without land as capital in limited liability companies, in the process based on Article 34 of the PT Law, clearly states the things that must be done if capital is entered in other forms. However, to ensure certainty in the process regarding capital inflows in other forms, in this case in the form of immovable objects other than land, an inbreng deed must be made before the Land Deed Making Officer for immovable property in the form of land or before a Notary for other immovable property. as legal proof of capital infusion into a limited liability company.